CHRONIC ENTEROCOLITIS IN CHILDREN (World Bulletin of Public Health, 2024)
Chronic enterocolitis in children is a chronic inflammatory disease affecting the intestine, especially the large and small intestine. It is characterized by symptoms such as abdominal pain, diarrhea, bloody stools, weight loss and poor growth. The disease includes different types including Crohn's disease, ulcerative colitis and indeterminate colitis. The exact cause of chronic enterocolitis in children is not fully understood, but it is thought to be due to a combination of genetic predisposition, environmental factors, immune system dysfunction, and changes in the gut microbiome. Diagnosis includes a comprehensive evaluation of the medical history, physical examination, laboratory tests, and imaging studies. The goal of treatment is to reduce inflammation, eliminate symptoms, accelerate healing, and improve overall health. It usually involves a combination of medications such as antiinflammatory drugs, immunosuppressants and biological therapies, as well as dietary therapy, including enteral nutrition alone or specialized diets. A multidisciplinary approach involving health care providers is necessary for comprehensive treatment. Chronic enterocolitis can have a significant impact on a child's daily life, including school attendance, social engagement, and emotional well-being. Strategies to address these issues include open communication with teachers, creating a supportive environment, and seeking psychological support if needed. Ongoing research aims to improve the understanding, diagnosis, and treatment of chronic enterocolitis in children. Advances in personalized medicine, the gut microbiome, and targeted therapies promise improved outcomes in the future